PENGARUH LABA DAN PERUBAHAN PIUTANG USAHA TERHADAP ARUS KAS OPERASI MASA MENDATANG - Sari, Melinda Wulan; Nurrasyidin, M.; Nugroho, Arif Widodo (Politeknik Negeri Semarang, 2024)
The aim of this study is to confirm the following effects Gross Profit, Net Income, and Changes in Account Receivable on Future Operating Cash Flow. As wellas the relations between the dependent independent and variables. The study's sampleis companies listed on LQ45 in 2017-2021. This study combined an associative strategy with a quantitative approach and used secondary data. This study used purposive sampling in the sample collecting. The analysis conducted in this study is, descriptive statistical analysis, classical assumption test, multiple linear regression analysis, hypothesis test and coefficient of determination analysis using SPSS version 25. The study's findings demonstrate the impact of Gross Profit, Net Income, and Changes in Account Receivable on Future Operating Cash Flow. Simultaneously, Gross Profit, Net Income, and Changes in Account Receivable affect Future Operating Cash Flow. The Adjusted R Square value of 71,5% and other factors explain the remaining 28,5%. Such as interest payment, payment oof claims, payment of other taxes, and retribution payment. Therefore, further researchers are anticipated to have the ability to employ variables not included in this study's analysis and add a wider sample not only limited to the companies listed on LQ45 in 2017-2021.